A differential electrometer for vector electric field measurements on a balloon platform - Jawahar, K.; Manu, S.; Gurubaran, S. (My University, 2016)
Vector measurements of middle atmospheric electric fields are mostly carried out using a double-Langmuir probe technique on platforms like balloons and rockets. High impedances (up to 1013 ohms) and low signal levels (~few millivolts) are the factors that are to be considered in the design of an electrometer for one such experiment. Here, we offer a simple circuit concept that invokes an instrumentation amplifier capable of meeting our several needs, namely generating the guard voltage, ultra-high impedance (1015 ohms) input terminals, femtoampere bias current, differencing, gain setting, etc. all in one package. A three-channel differential electrometer was developed based on this concept and flown on a high-altitude balloon platform. Results reveal that the instrument is capable of detecting weak electric field variations at stratospheric altitudes.
Keywords: Atmospheric electric field; Atmospheric electricity; Stratosphere; Double-Langmuir probe technique; Balloon experiment